Whānau Māori and their experiences of attention-deficit/hyperactivity disorder : implications for clinical practice : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Manawatū, New Zealand - Tipene, Charlene Mereana (Massey University, 2023)
Health care in New Zealand (NZ) is based on the ideal of universal health coverage for all. However, for many Māori health inequities exist in health outcomes and in access to services which adequately meet the needs of whānau Māori. Researchers have considered explanations (and solutions) for this situation, including whether health services are able to meet the cultural needs of Māori clients through a more holistic approach. Rather than considering this generally for all services, this research considers this specifically in relation to Attention-Deficit Hyperactivity Disorder (ADHD). Alongside core symptoms of hyperactivity, impulsivity, and inattention, for there to be a diagnosis of ADHD there must be associated functional impairment and diffuse impact of behavioural symptoms in multiple domains of a person’s life. This means that ADHD is well suited to the application of holistic understandings of wellbeing, such as those that exist in mātauranga Māori. A lack of research about ADHD among Māori highlights a need for research which explores the experiences of tamariki Māori and their whānau as they navigate ADHD diagnosis and treatment. This research used a Māori-centred framework and throughout, was guided by He Awa Whiria (Gillon & Macfarlane, 2017) which emphasises the importance of drawing together cultural and clinical knowledge. There were three main objectives: to understand the experiences of whānau Māori with a child assessed and treated for ADHD; to describe how whānau understood and accommodated ADHD behaviours before diagnosis; and to identify any barriers or facilitators for whānau Māori in accessing assessment and/or treatment. Semi-structured interviews took place with 10 whānau members, representing 13 young people who had been diagnosed with ADHD. The interview responses were analysed using (codebook) thematic analysis. The main findings revealed firstly that there were different levels of knowledge about ADHD among caregivers and some whānau struggled to know where to begin, to get support; secondly, it was difficult to access the service, and there was a lack of ongoing support available other than medication; and thirdly, while in all cases medication was offered as treatment, whānau found this a difficult decision to make for their child, preferring a more holistic approach. Most whānau were not asked about their cultural background or beliefs during assessment and half of the participants would have accessed a kaupapa Māori service if available. The implications of the findings for clinical practice are discussed with recommendations for how to blend cultural and clinical knowledge to ultimately benefit whānau Māori and achieve the best possible outcomes.
Keywords: Attention-deficit hyperactivity disorder; Diagnosis; Treatment; Māori (New Zealand people); Mental health; Mental health services; Hauora whānau; Hauora hinengaro; Tahumaero; Whānau Māori, tamariki, rangatahi, mātauranga, tikanga, ADHD, ADD, assessment, case formulation, clinical practice, health equity; Māori Doctoral Thesis; 451013 Mātauranga hinengaro kaupapa Māori (Māori psychology); 520302 Clinical psychology